Improved water management of coal conversion processes by preliminary absorption of halides (McKee (Davy) Engineers and Constructors, Cleveland, OH (USA), 1979)
For coal conversion processes that employ wet cleaning of gases, such as those supplying cooled gas to storage or to distribution systems, gas condensates are produced that contain various pollutants. Condensates from gases derived from coal may contain gas borne particulates, tars, oils or water solubles such as ammonia, chlorides, cyanides, fluorides, phenols and sulfides. The upgrading of contaminated gas condensates to service water quality by treatment oriented technology can entail a complex sequence of processing including desalination. A modified wet gas cleaning system was proposed by Davy McKee Corporation as offering promise of improving the practicality of reuse of gas condensates from coal gasification. This production oriented technology replaced the conventional single stage quench of the gases with a system incorporating a two-stage quench. The concept advocated the removal of particulates and the absorption of halides and other strong electrolytes in a controlled first stage quench that would condense a small fraction of the water vapor contained in the product gas. This low volume primary condensate would be purged from the system. The major fraction of condensate collected by the second stage quench would be relatively free of strong electrolytes and would be amenable to processing for reuse without resort to desalination technology. The volatile weak electrolytes in the secondary condensate would be removed by steam stripping and organic substances would be removed by biological treatment. The proposal is more advantageous with coals containing more than average amounts of chlorides.